The Role of Social Media in Health Education of Cervical Cancer: Peran Media Sosial Dalam Pendidikan Kesehatan Kanker Serviks - Febry Ramadhani Suradji; Ade Yuni Sahruni (Politeknik Karya Persada Muna, 2022)
Background: Currently, cervical cancer is still a reproductive health problem faced by many women. The importance of health communication between the public and health professionals through online media is an effort that can be done in this 5.0 era. This research was conducted to find out how the role of social media in health education for cervical cancer. Method: This study uses a literature study method where researchers collect information from books and journals related to the topic studied using the keywords Health education and cervical cancer. The time of the search was carried out from May-June 2022. The inclusion criteria in this study were all journals related to health education through social media and cervical cancer published in 2018-2022. There were 364 studies found, and after screening, there were 7 studies that met the inclusion criteria.Results: The results showed that social media is an effective information medium used in disseminating information related to cervical cancer.Conclusions: Social media plays an important role in increasing knowledge and behavior of cervical cancer prevention, motivating women to carry out an IVA (Visual Acetic Acid Inspection) examination, as a medium for information seeking, prevention and treatment of cervical cancer. This is also supported by the number of social media currently developing free or paid consultation applications to get information related to cervical cancer.Keyword: Education, Social Media, Cervical Cancer